Calvin Coolidge papers - Coolidge, Calvin, 1872-1933.
White House office files consisting of incoming correspondence, draft replies, carbon copies of outgoing letters from Coolidge or one of his secretaries (Edward Tracy Clark, Everett Sanders, and C. Bascom Slemp), incoming telegraph messages, appointment books, and three volumes of names and addresses of White House guests. Includes telegraph messages from the first months of the Herbert Hoover administration.
Correspondents include Lincoln C. Andrews, James M. Beck, Mark L. Bristol, William Smith Culbertson, Alfred Pearce Dennis, Charles Schuveldt Dewey, Henry Percival Dodge, Milton Stover Eisenhower, John Gilman Foster, Howard M. Gore, Joseph C. Grew, John Hays Hammond, Herbert Hoover, Charles Evans Hughes, William Marion Jardine, Frank B. Kellogg, Charles A. Lindbergh, Nicholas Longworth, David Lynn, Hanford MacNider, George H. Moses, Harry S. New, Peter Norbeck, Robert Edwin Olds, William Joseph O'Toole, William Phillips, Gifford Pinchot, Miles Poindexter, Atlee Pomerene, John Dyneley Prince, Theodore Douglas Robinson, William Worthington Russell, Henry Cantwell Wallace, Ira Kent Wells, Roy Owen West, Frank B. Willis, Garrard Bigelow Winston, and Leonard Wood.
Microfilm edition of Series 1-3 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
U.S. president and businessman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Andrews, Lincoln C. -- 1867-1950 -- Correspondence; Beck, James M. -- 1861-1936 -- Correspondence; Bristol, Mark L. -- 1868-1939 -- Correspondence; Clark, Edward Tracy, -- 1878-1935 -- Correspondence; Culbertson, William Smith, -- 1884-1966 -- Correspondence; Dennis, Alfred Pearce, -- 1869-1931 -- Correspondence; Dewey, Charles Schuveldt, -- 1880-1980 -- Correspondence; Dodge, Henry Percival, -- 1870-1936 -- Correspondence; Eisenhower, Milton Stover, -- 1899-1985 -- Correspondence; Foster, John Gilman, -- 1859-1931 -- Correspondence; Gore, Howard M. -- Correspondence; Grew, Joseph C. -- 1880-1965 -- Correspondence; Hammond, John Hays, -- 1888-1965 -- Correspondence; Hoover, Herbert, -- 1874-1964.; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Jardine, William Marion, -- 1879-1955 -- Correspondence; Kellogg, Frank B. -- 1856-1937 -- Correspondence; Lindbergh, Charles A. -- 1902-1974 -- Correspondence; Longworth, Nicholas, -- 1869-1931 -- Correspondence; Lynn, David, -- 1873-1961 -- Correspondence; MacNider, Hanford, -- 1889-1968 -- Correspondence; Moses, George H. -- 1869-1944 -- Correspondence; New, Harry S. -- 1858-1937 -- Correspondence; Norbeck, Peter, -- 1870-1936 -- Correspondence; Olds, Robert Edwin, -- 1875-1932 -- Correspondence; O'Toole, William Joseph -- Correspondence; Phillips, William, -- 1878-1968 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Poindexter, Miles, -- 1868-1946 -- Correspondence; Pomerene, Atlee, -- 1863-1937 -- Correspondence; Prince, John Dyneley, -- 1868-1945 -- Correspondence; Robinson, Theodore Douglas, -- 1883-1934 -- Correspondence; Russell, William Worthington, -- 1859- -- Correspondence; Sanders, Everett, -- 1882-1950 -- Correspondence; Slemp, C. Bascom -- 1870-1943 -- Correspondence; Wallace, Henry Cantwell, -- 1866-1924 -- Correspondence; Wells, Ira Kent, -- 1871- -- Correspondence; West, Roy Owen, -- 1868-1958 -- Correspondence; Willis, Frank B. -- 1871-1928 -- Correspondence; Winston, Garrard Bigelow, -- 1882-1955 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; White House (Washington, D.C.); United States -- Politics and government -- 1923-1929.; United States -- Politics and government -- 1929-1933.; Washington (D.C.) -- Social life and customs; Businessmen; Presidents -- United States